Monologika; Retorika untuk Tabligh Islam (Menelusuri sejarah menemukan arah) - Ridwan, Aang (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2009)
Retorika has the significant positionÂ in oftimalizingÂ tablighs aim attainment. The top aspect of tabligh that utilizes rhetorics can be recognized on mubalighâs skill in getting language and managing knowledge that will be passed to audiencesÂ so tablighs message becomes sistematic. In developing history of the monologics rhetoric has recognized three forms of rhetorics, there are elocusionis ,Â Belles lettris , and teste faculty. (1 )Â elocusionis, focusing its study on technic problem of oration forwarding, (2 ) Belletrist, this rhetoric form Â really accentuates aesthetical lingual and esthetic facet order on writing. (3 ) teste faculty rhetorics, it emphasize teste importance in rhetoric.